2017
DOI: 10.1002/joc.5060
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to link climate change data provision and user needs: Perspective from the COST‐action VALUE

Abstract: The application of climate change impact assessment (CCIA) studies in general and especially the linkages between different actor groups typically involved is often not trivial and subject to many limitations and uncertainties. Disciplinary issues like competing downscaling approaches, imperfect climate and impact model data and uncertainty propagation as well as the selection of appropriate data sets are only one part of the story. Interdisciplinary and transdisciplinary challenges add to these, as climate da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
(57 reference statements)
1
31
0
Order By: Relevance
“…This also corresponds to experiences gathered in other countries (Formayer et al, 2011;MeteoSwiss, 2016) andprojects (e.g., Swart andAvelar, 2011;Hewitt et al, 2013;Groot et al, 2014;Roessler et al, 2017). Thus, even though we focus on the ReKliEs-De project workshop, the questions and problems that were formulated there are shared by other users -albeit perhaps to different degrees.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This also corresponds to experiences gathered in other countries (Formayer et al, 2011;MeteoSwiss, 2016) andprojects (e.g., Swart andAvelar, 2011;Hewitt et al, 2013;Groot et al, 2014;Roessler et al, 2017). Thus, even though we focus on the ReKliEs-De project workshop, the questions and problems that were formulated there are shared by other users -albeit perhaps to different degrees.…”
Section: Discussionsupporting
confidence: 63%
“…Presently, a growing number of institutions, projects, and initiatives address this gap (e.g., Groot et al, 2014;Harold et al, 2016;Roessler et al, 2017). Additionally, the Global Framework for Climate Services (GFCS, www.wmo.int/gfcs/) has started a discussion towards an ethical framework for climate services, which calls for integrity, transparency, humility, and collaboration when providing climate services.…”
Section: H Huebener Et Al: Deriving User-informed Climate Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The VALUE project (Maraun et al, ; Gutiérrez et al, ; Maraun et al, ) included a stakeholder/end‐user survey (62 participants) that found temperature and precipitation were the top two climate variables of interest. The required accuracy was ±10–20% for temperature and ±10–50% for precipitation and temporal and spatial resolutions of daily and point or < 1 km are desired (Rössler et al, ). Due to large fractional errors that can arise close to 0°C, we assume a mean air temperature of 15°C and equate a ± 15% uncertainty to ±2.25°C.…”
Section: Evaluation In the Context Of The Value End‐user Surveymentioning
confidence: 99%
“…platform which can be open, shareable, knowledgeable, and contributable globally [7][8][9]. 3 of 15 Spatial data are dramatically increasing in volume and complexity, just as the users of these data in 95 the scientific community and the public are rapidly increasing in number [10][11].…”
mentioning
confidence: 99%